Die großen Abweichungen für die homogenen Markoffschen Ketten - Misevičius, E. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Мисявичюс. Локальная теорема с большими уклонениями для однородных цепей Маркова E. Misevičius. Didelių nukrypimų homogeninėse Markovo grandinėse lokalinė teorema